(untitled) (International Journal of Architecture and Urbanism, 2022)
Girsang Sipangan Bolon District, Simalungun Regency, is one of the entrance gates to Lake Toba and has an area of ​​126 km2 with a population of 18,915 people. Parapat Village is the largest sub-district in this sub-district, and has long been famous for its tourism. Defining and Using Indicators is the main component in the process of planning and managing sustainable tourism, so this will use the main issues and indicators of sustainable tourism development in a tourist destination. This study examines waste management in Girsang Sipangan Bolom District in an effort to support Lake Toba. Implementing policies by reducing the use of chemicals that can harm the environment, reducing waste to the environment and the use of waste disposal systems, and supervising newly established facilities.